A Preliminary Inquiry Into the Potential Mechanism of Huang-Lian-Jie-Du Decoction in Treating Rheumatoid Arthritis via Network Pharmacology and Molecular Docking - Li, Chenlu; Pan, Jingjing; Xu, Chang; Jin, Zhenlin; Chen, Xupeng (Frontiers in Cell and Developmental Biology, 2022)
Huang-Lian-Jie-Du decoction (HLJDD) has been applied to treat inflammation-associated diseases for thousands of years in China. However, the concrete molecular mechanism of HLJDD in the treatment of rheumatoid arthritis (RA) remains unclear. In this work, network pharmacology and molecular docking were used to analyze the potential active ingredients, drug targets, and key pathways of HLJDD on treating RA. A total of 102 active compounds with corresponding 189 targets were identified from HLJDD and 41 common targets were further identified by intersecting with RA-related targets. Functional enrichment analysis was performed to screen the biological pathways associated with RA and 10 hub targets were further identified through constructing the protein-protein interaction (PPI) network of common targets, which were mainly enriched in the interleukin 17 (IL-17) signaling pathway, tumor necrosis factor (TNF) signaling pathway and Toll-like receptor signaling pathway. Furthermore, a complex herbs-ingredients-hub targets-disease network was successfully constructed and the results of molecular docking exhibited that these vital ingredients of HLJDD had a stable binding to the hub targets. Among these ingredients, quercetin (MOL000098) was the most significant molecule with stable binding to all the targets, and PTGS2 was considered as the most important target with multiple regulations by the most active ingredients. In vitro, we sucessfully validated the inhibitory role of quercetin in cellular proliferation of Human RA fibroblast-like synoviocyte cell line (MH7A cells). These findings indicated that the potential mechanisms of HLJDD for RA treatment might be attributed to inhibiting the immune-inflammatory response, reducing the release of chemokines, and alleviating the destruction of extracellular matrix (ECM) in the synovial compartment.